2008
DOI: 10.1016/j.cbi.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the reaction of carbachol with acetylcholinesterase by thioflavin T fluorescence and acetylthiocholine hydrolysis

Abstract: Acetylcholinesterase (AChE) contains a narrow and deep active site gorge with two sites of ligand binding, an acylation site (or A-site) at the base of the gorge and a peripheral site (or P-site) near the gorge entrance. The P-site contributes to catalytic efficiency by transiently binding substrates on their way to the acylation site, where a short-lived acyl enzyme intermediate is produced. Carbamates are very poor substrates that, like other AChE substrates, form an initial enzyme-substrate complex and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…5). This approach can be monitored by either thioflavin T fluorescence or simultaneous acetylthiocholine hydrolysis (24), and reactions monitored by acetylthiocholine hydrolysis are illustrated in Fig. 5A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). This approach can be monitored by either thioflavin T fluorescence or simultaneous acetylthiocholine hydrolysis (24), and reactions monitored by acetylthiocholine hydrolysis are illustrated in Fig. 5A.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve k 12 rate constants that were second order and corresponded to eq. 6, carbachol was maintained at 0.5 mM (where K app ≡ K M was 5.7 mM (24)). Acetylthiocholine concentrations were 50 µM to minimize [S 2 ]/K app2 in eq.…”
Section: Resultsmentioning
confidence: 99%
“…Melanogenesis inhibitors are used to whiten the skin of patients treated with pigmentation disorders, such as overproduction of melanin (Hartong et al, 2006) and Addison's disease (Pandya and Guevara, 2000). Oliveira et al (2011) found the anticholinesterase activity of CNSL constituents, although cardol, cardanol, carbachol and anacardic acids were previously reported for their cholinesterase inhibitory activity (Rosenberry et al, 2008). Some of the biological activities of LCC and its chemical compounds are presented in Table 1.…”
Section: A Occidentale and Its Biological Rolesmentioning
confidence: 99%
“…Moreover, the non-ionic character of these oximes should increase the lipophilicity and BBB penetration of the conjugates. Although we know that the structural and functional differences between human, animal and electric eel AChE may result in a different affinity and reactivity of oximes, we have been working with electric eel AChE due to its ready availability, which facilitates screening assays.Some reports have demonstrated that an allosteric enhancement of reactivation of carbamoylated or phosphorylated acetylcholinesterases occurred through PAS occupation by peripheral site ligands [47][48][49] . furthermore, it was also shown that oxime-mediated dephosphorylation was accelerated in the presence of a ligand with affinity for the PAS 50 .…”
mentioning
confidence: 99%
“…Some reports have demonstrated that an allosteric enhancement of reactivation of carbamoylated or phosphorylated acetylcholinesterases occurred through PAS occupation by peripheral site ligands [47][48][49] . furthermore, it was also shown that oxime-mediated dephosphorylation was accelerated in the presence of a ligand with affinity for the PAS 50 .…”
mentioning
confidence: 99%